The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-311x2010000900011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de fraturas vertebrais e fatores de risco em mulheres com mais de 60 anos de idade na cidade de Chapecó, Santa Catarina, Brasil

Abstract: Fraturas são o principal agravo relacionado à fragilidade óssea na pós-menopausa, representando aumento de risco de novas fraturas, mortalidade e custos. Nosso objetivo foi verificar a ocorrência de fratura vertebral por fragilidade e relacioná-la com fatores demográficos, comportamentais e clínicos em uma população brasileira. Foi feito um estudo transversal com seleção por amostragem aleatória estratificada de mulheres idosas residentes em Chapecó, Santa Catarina, Brasil. A amostra foi constituída por 186 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(44 reference statements)
0
8
0
2
Order By: Relevance
“…This is corroborated by Siqueira et al 26 , when identifying higher occurrence of osteoporotic fractures in men, with high incidence or mortality and morbidity and significant costs. In the same direction, Oliveira et al 27 identified a 50% higher risk of fractures in men when comparing to women, considering a sample of 3,214 individuals in the city of Pelotas (RS).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is corroborated by Siqueira et al 26 , when identifying higher occurrence of osteoporotic fractures in men, with high incidence or mortality and morbidity and significant costs. In the same direction, Oliveira et al 27 identified a 50% higher risk of fractures in men when comparing to women, considering a sample of 3,214 individuals in the city of Pelotas (RS).…”
Section: Discussionmentioning
confidence: 96%
“…This expenditure pattern may be associated to the climatic, racial and genetic factors 27 . This data is also corroborated by Silveira 28 , in studies carried out in the Southeast and Northeast regions, in which it was observed a possible influence of the climatic conditions in order to justify the found data.…”
Section: Discussionmentioning
confidence: 99%
“…Pode-se afirmar que atividade física, tabagismo, manejo do estresse, consumo de álcool, hábitos alimentares, contato interpessoal, práticas religiosas, condições socioeconômicas e presença/ausência de DCNT são fatores que influenciam o estilo de vida da população idosa (BORGES;SEIDL, 2012;HARA et al, 2008;PAGOTTO;NAKATANI;SILVEIRA, 2011;PIMENTA et al, 2008;SILVA et al, 2014;ZAITUNE et al, 2007). No que diz respeito aos fatores de risco relacionados ao estilo de vida que influenciam negativamente a saúde do idoso, pode-se afirmar que inatividade física, tabagismo, presença de DCNT, alimentação inadequada, dislipidemia, consumo excessivo de álcool, obesidade, hipercolesterolemia, alterações na glicemia, resistência à insulina e o avanço da idade foram destacados (BORGES;SEIDL, 2012;COSTA et al, 2014;FERREIRA et al, 2010;HARA et al, 2008;OLIVEIRA et al, 2010;PAGOTTO;NAKATANI;SILVEIRA, 2011;PIMENTA et al, 2008;SIMÕES;LEITE, 2007;SILVA et al, 2014;VITOI et al, 2015;VIEIRA;PEIXOTO;SILVEIRA, 2014;ZAITUNE, 2007).…”
Section: R E S U L T a D O Sunclassified
“…Segundo Oliveira et al (2010), a ocorrência de fraturas decorrentes da fragilidade óssea corresponde a importante aumento na morbimortalidade entre idosos. No estudo desses autores, optou-se por verificar a ocorrência de fratura vertebral por relacionar-se à osteoporose e representar risco elevado para a ocorrência de novas fraturas.…”
Section: 2 F a T O R E S D E R I S C O P A R A D C N Tunclassified
“…One study by Mayo Clinic, with data from 2000 to 2011, reveals that osteoporotic fractures accounted for 4.9 million hospitalizations with an expenditure of US$ 5.1 billion, higher than that caused by acute myocardial infarction (2.9 million and US$ 4.3 billion), stroke (3.3 million and US$ 3 billion) and breast cancer (700,000 and US$ 0.5 billion). 5 In Brazil, there are still few data and information on the occurrence of osteoporotic fractures, despite the large number of affected patients, high morbidity and mortality rates due to chronic-degenerative diseases, and the increased life expectancy, which contributes to the increase in numbers related to this public health problem; therefore, more studies on the subject are needed. Thus, this study aims to evaluate the involvement of orthopedists and residents in Orthopedics with fragility fractures, in its clinical, therapeutic, and social aspects.…”
Section: Introductionmentioning
confidence: 99%